SNARE-complex disassembly by NSF follows synaptic-vesicle fusion - Littleton, J. Troy (The National Academy of Sciences, 2001)
Soluble N-ethylmaleimide-sensitive fusion attachment protein receptor (SNARE)-mediated fusion of synaptic vesicles with the presynaptic-plasma membrane is essential for communication between neurons. Disassembly of the SNARE complex requires the ATPase N-ethylmaleimide-sensitive fusion protein (NSF). To determine where in the synaptic-vesicle cycle NSF functions, we have undertaken a genetic analysis of comatose (dNSF-1) in Drosophila. Characterization of 16 comatose mutations demonstrates that NSF mediates disassembly of SNARE complexes after synaptic-vesicle fusion. Hypomorphic mutations in NSF cause temperature-sensitive paralysis, whereas null mutations result in lethality. Genetic-interaction studies with para demonstrate that blocking evoked fusion delays the accumulation of assembled SNARE complexes and behavioral paralysis that normally occurs in comatose mutants, indicating NSF activity is not required in the absence of vesicle fusion. In addition, the entire vesicle pool can be depleted in shibire comatose double mutants, demonstrating that NSF activity is not required for the fusion step itself. Multiple rounds of vesicle fusion in the absence of NSF activity poisons neurotransmission by trapping SNAREs into cis-complexes. These data indicate that NSF normally dissociates and recycles SNARE proteins during the interval between exocytosis and endocytosis. In the absence of NSF activity, there are sufficient fusion-competent SNAREs to exocytose both the readily released and the reserve pool of synaptic vesicles.